Collaborative group and teacher formation: (trans)formation dialogues with a fledging university professor - doi: 10.4025/actascieduc.v35i2.20307 - Maria Aparecida de Souza Perrelli; Luciana Virgili Pedroso Garcia (Universidade Estadual de Maringá, 2013)
Discussions on university teaching, teaching initiation and the necessary teacher support during the initial phase of their career are provided. The above mentioned discussions foregrounded a study by a research-formation collaborative Group. Sharing participants in the Group were involved in reflections on their professional practice to (trans)form themselves in the process. The text focused on a Group member, a fledging female professional in university teaching, and the support provided by co-trainers during this difficult phase in her career. Support comprised the provision of conditions for dialogues with the teacher, prompting her to understand the reasons that underlay their practice. Different strategies were used, esp the 'formation letters'. The above contributed towards the production of an autobiographical narrative in which the professor reflected on her formation process as a professor. The reflective narratives on the teacher's life, produced within the Group's mediation and shared with its members, constituted important formation themes not merely for the teacher but also for those who interacted with her in the collaborative Group.